(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The attention of civil society organizations, governments and international non-governmental organizations in recent years has focused on the acute practices adopted by companies with the aim of reducing the tax burden, and the results of these practices have a negative impact on the tax revenues that the state uses to finance public needsThe aim of the research is to measure the impact of the voluntary disclosure of companies on tax planning for the period from 2011 to 2015 and the research community is in the General Tax Authority. The research sample is 6 companies within the private sector in the financial, banking, insurance and industrial fields. The research was based on a special model to measure the optional disclosure, while using a special form. To measure tax planning by relying on the effective tax rateThe results of the research resulted in the absence of an effect of the voluntary disclosure of companies in tax planning and the acceptance of the alternative hypothesis that denies the existence of the relationship between the two variables. The research concluded that the level of voluntary disclosure was weak in the researched companies. They also practice tax planning activities in varying proportions from year to year with a greater percentage in the sector. Industrial and imsuranfe.